1997
DOI: 10.1002/(sici)1096-9861(19971208)389:1<34::aid-cne3>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of ipsilateral corticocortical inputs to the orofacial region of the primary motor cortex in the macaque monkey

Abstract: An anatomical approach to possible areas in the cerebral cortex involved in somatic motor behavior is to analyze the cortical areas containing neurons that connect directly to the primary motor cortex (MI). To define the cortical areas related to orofacial movements, we examined the distribution of cortical neurons that send their axons to the orofacial region of the MI in the macaque monkey. Injections of retrograde tracers into the electrophysiologically identified orofacial region of the MI revealed that la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 52 publications
2
38
1
Order By: Relevance
“…2), which were representative of sulcal and gyral locations in many other regions of the cortex. Although previous macaque anatomical studies have shown that each of these cortical positions gives rise to long-range axonal projections (9,28,(43)(44)(45)(46)(47), we found that the resulting track lines in most cases failed to escape the local white matter environment. In fact, of the four seeds shown in this example only seed 2, on the precentral gyrus, extended beyond the superficial association fibers and into the deeper white matter.…”
Section: Resultscontrasting
confidence: 80%
“…2), which were representative of sulcal and gyral locations in many other regions of the cortex. Although previous macaque anatomical studies have shown that each of these cortical positions gives rise to long-range axonal projections (9,28,(43)(44)(45)(46)(47), we found that the resulting track lines in most cases failed to escape the local white matter environment. In fact, of the four seeds shown in this example only seed 2, on the precentral gyrus, extended beyond the superficial association fibers and into the deeper white matter.…”
Section: Resultscontrasting
confidence: 80%
“…We speculated that this strong connectivity between the M l face area and CMA may be explained by postulating the ventral part of M l (face area) and CMA to be part of the same circuit, working together with the lateral part of the facial nucleus, to pro vide the lower face motor innervation [Morecraft et al, 2004]. Indeed, studies in nonhuman primates have demon strated that the frontal and cingulate facial areas are selec tively and reciprocally interconnected at the cortical level [Morecraft and Van Hoesen, 1992;Morecraft et al, 1996Morecraft et al, , 2001Muakkassa and Strick, 1979;Tokuno et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that this strong connectivity between the M l face area and CMA may be explained by postulating the ventral part of M l (face area) and CMA to be part of the same circuit, working together with the lateral part of the facial nucleus, to pro vide the lower face motor innervation [Morecraft et al, 2004]. Indeed, studies in nonhuman primates have demon strated that the frontal and cingulate facial areas are selec tively and reciprocally interconnected at the cortical level [Morecraft and Van Hoesen, 1992; Morecraft et al, 1996 Morecraft et al, , 2001 Muakkassa and Strick, 1979;Tokuno et al, 1997].The results of the analysis of our previous motor-related data and those of the meta-analysis were concordant in defining the spatial positions of the upper limb (hand) and lower limb (foot) activations; moreover, they all showed the volume of activation to be bigger for hand rather than foot movement. In the results of the FC analysis of our previous data, as well as in those of the present rs-fMRI study, the center of mass of the foot representation in the medial wall was located more dorsally with respect to the results of the meta-analysis.…”
mentioning
confidence: 99%
“…In macaque monkeys, face-M1 receives corticocortical inputs from the ventral division of the premotor cortex, whose counterpart cortical regions in humans are implicated in speech [37]. In patients with persistent developmental stuttering, the white matter of speech-relevant brain regions in the left motor and premotor regions display abnormal fractional anisotropy values, indicating functional disconnection between speech-relevant brain areas [38].…”
Section: Discussionmentioning
confidence: 99%